Unveiling the Hidden Dynamics Behind Effective Credit Card Sales Promotions - Yuardi Hendrastiawan; Nur Khusniyah Indrawati; Mugiono Mugiono (Penerbit Goodwood, 2026)
Purpose: This study aims to explore the strategic role of sales personnel characteristics and promotion duration in enhancing the effectiveness of credit card sales promotions across various strategic locations. Methodology: Using a qualitative case study approach, the research analyzed promotional activities and sales staff performance at malls, restaurants, and office buildings through interviews and observations, and thematic analysis. Results: The findings revealed that selecting sales personnel with interpersonal skills aligned with target customer profiles significantly improved consumer engagement and purchase conversion. Additionally, tailoring promotion duration to consumer behavior and the environment, such as longer promotions in high-traffic areas and shorter bursts in controlled settings, optimizes consumer interest while minimizing fatigue. Conclusions: This study innovatively integrates the temporal dimension and situational adaptability, demonstrating that an optimal promotion duration must balance urgency and consumer engagement to avoid message fatigue or underexposure. Furthermore, the nuanced approach to selecting sales staff, considering interpersonal skills, adds depth to conventional sales performance models by emphasizing the importance of matching sales strategies to specific promotional environments. Limitations: This study focused on a single business and specific products, which may limit its generalizability. Contributions: These results are explained through the application of situational selling theory and consumer attention dynamics. This study advances the existing knowledge by integrating human resource considerations with temporal factors in sales promotion strategies. Marketers should design promotion plans that consider both the contextual and psychological elements of consumer behavior to improve effectiveness.